Toksisitas beberapa jenis fungisida komersial pada serangga penyerbuk, Trigona (Tetragonula) laeviceps Smith - Ida Kinasih; Rusdy Syachrul Nugraha; Ramadhani Eka Putra; Agus Dana Permana; Mia Rosmiati (Jurnal Entomologi Indonesia, 2017)
Fungicide is one of the common pesticide applies in agriculture. Even though fungicide is specifically designed to prevent growth of fungi, some studies reported neurotoxic effects of fungicide to some tested animals. Therefore there are concerns about the possible determintal effects of fungicide to beneficial non target organisms, like pollinating insects. This study was conducted to determine the toxicity of commercial fungicide to pollinator, Trigona (Tetrgonula) laeviceps Smith, by determining the LD50 and hazard quotient (HQ). The fungicides tested were triazole (tridimefon and difenoconazole), propamorcab (propamocarb HCl), and dithiocarbamate (mancozeb and propineb). Forager bees were collected and anasthesized by exposing the bees to low temperature (-10 oC) for 1 min. About 1 µl of tiadimefon (6,25; 12,5; 25; 37,25; 50 µg/bee), difenoconazole (1,25; 2,5; 5; 6,25; 12,5; 25 µg/bee), propamocarb HCl (72.,25; 144,5; 216,6; 361,25; 433,5 µg/bee), mancozeb (1,6; 3,2; 4,8; 6,4; 8 µg/bee), and propineb (0.9; 1.8; 2.7; 6; 8.4; 16.8; 25.2 µg/bee) were applied using topical application on dorsal area of bees. Ten bees were used for each concentration and replicated 3 times. Mortality of bees was recorded for 48 hours. Results showed that LD50 and HQ for each tested fungicide were as follow: triadimefon LD50 13.43 ±1.78 µg/bee, HQ = 18.62; difenoconazole LD50 9.25 ± 1.21 µg/bee, HQ = 27.03; propamocarb HCl LD50 270.45 ± 19.48 µg/bee, HQ = 14.34; mancozeb LD50 3.75±0.47 µg/bee, HQ = 512; and propineb LD50 9.71 ±2.20 µg/bee, HQ = 144.18. Among all 5 tested fungicide, two fungicide, mancozeb and propineb, has intermediate level of toxicity to foragers of T. laeviceps and could produce determintal effect to colony.